2010
DOI: 10.1002/hbm.20968
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and default‐mode resting state networks: Do male and female brains “rest” differently?

Abstract: Variability in human behavior related to sex is supported by neuroimaging studies showing differences in brain activation patterns during cognitive task performance. An emerging field is examining the human connectome, including networks of brain regions that are not only temporally-correlated during different task conditions, but also networks that show highly correlated spontaneous activity during a task-free state. Both task-related and task-free network activity has been associated with individual task per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
7
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 64 publications
(118 reference statements)
6
98
7
1
Order By: Relevance
“…However, these differences likely did not influence the results of the present study. Indeed, a previous study of major resting-state networks (executive control, salience, and default mode) in males and females found no gender-based differences (Weissman-Fogel et al, 2010). The authors also further argued that restingstate fMRI studies do not need to be controlled for gender (Weissman-Fogel et al, 2010).…”
Section: Limitationsmentioning
confidence: 95%
“…However, these differences likely did not influence the results of the present study. Indeed, a previous study of major resting-state networks (executive control, salience, and default mode) in males and females found no gender-based differences (Weissman-Fogel et al, 2010). The authors also further argued that restingstate fMRI studies do not need to be controlled for gender (Weissman-Fogel et al, 2010).…”
Section: Limitationsmentioning
confidence: 95%
“…A previous study has shown no significant differences between the sexes in functional connectivity during the resting state. 28 Pre-HD and symp-HD individuals underwent gene testing before enrolment in the study, were assessed by a clinician (A.C. or P.C.) and underwent a Unified Huntington's Disease Rating Scale (UHDRS) motor assessment.…”
Section: Participantsmentioning
confidence: 99%
“…El tiempo de medición oscila entre los 6 y 10 minutos, esto con el fin de evitar cambios en el estado de vigilia y además permitir que se obtengan suficientes imágenes para la identificación de las RER (25). Con respecto al sexo de los voluntarios, no se han encontrado diferencias significativas en los patrones de las RER entre hombres y mujeres (26).…”
Section: Adquisición De Imágenes En Estado De Reposounclassified